Pendampingan UMKM Kuliner Berbasis Potensi Lokal di Kecamatan Gerung dan Sekitarnya dalam Meningkatkan Daya Saing dan Keberlanjutan Usaha di Kabupaten Lombok Barat - Ida Ayu Nursanty; Lalu Takdir Jumaidi; Lilik Handajani; Baiq Anggun Hilendri Lestari; Elin Erlina Sasanti; Wahyu Jekti Handayani (MAN 4 Kota Pekanbaru, 2026)
Culinary Micro, Small, and Medium Enterprises (MSMEs) play a strategic role in promoting regional economic development through job creation, income generation, and the utilization of local resources. However, many culinary MSMEs in Gerung District and its surrounding areas face challenges related to limited product innovation, weak business management, inadequate financial record-keeping, and the underutilization of digital marketing. These constraints reduce business competitiveness and long-term sustainability. This community service program aimed to strengthen the capacity of culinary MSMEs through assistance in production, business management, and local potential-based marketing. A participatory approach was employed, involving needs assessment, training, mentoring, monitoring, and evaluation. The results indicate improved partner understanding of product innovation, simple financial recording, product branding, and digital marketing practices. The mentoring program also enhanced managerial capabilities and encouraged more systematic and sustainable business management. This program is expected to serve as a practical model for empowering local potential-based culinary MSMEs and strengthening the local economy in West Lombok Regency.